(untitled) (Latin-American Journal of Computing, 2017)
In this research work, the results of applying DeepLearning prediction models to identify the digit of an image,that contains a handwritten number of the MNIST database, arepresented. This set of dataset was acquired from the competitionof Kaggle: Digit Recognizer. The following process was applied:First, image preprocessing techniques were used, which focuson obtaining a pretty clear image and to reduce the size ofthe same, these objectives that are achieved with Otsu Method,transformed from Haar Wavelet and the Principal ComponentAnalysis (PCA), thus obtaining as a result, one set of new datasetto be evaluated. Second, the Deep Learning MxNET and H2omodels, which were executed in the statistical language R, wereapplied to these datasets obtained, this way, several predictionswere acquired. Finally, the best obtained predictions in theexperiment were sent to the Digit Recognizer competition, andthe results of this evaluation scored 99,129% of prediction.